NEGOTIATION STRATEGIES FOR MAXIMIZING RELATIONSHIP VALUE IN CORPORATE BANKING - Felicia Alvina; Pri Hermawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid evolution of corporate banking in Indonesia has heightened competition among financial institutions, where interest-rate negotiations remain the most visible yet least sustainable differentiator. Relationship Managers (RMs) often continue to rely on rate-based concessions to secure deals despite having instututional efforts to standardize pricing. This approach has resulted in short-term profitability at the expense of long-term relationship value, client stickiness, and cross-product synergy. As a result, it is necessary to investigate how negotiation in corporate banking can transform from transactional rate bargaining into strategic relationship management. The purpose of this research is to analyze and formulate a comprehensive negotiation framework that allows RMs to optimize relationship value creation using structured decision tools and cross-functional collaboration. This study aims to answer four core research questions: how multi-criteria decision-making frameworks such as SMART can guide negotiation evaluation; what alternative strategies can be developed based on empirical insights from RMs and Product Partners; how RMs can leverage negotiation concepts such as BATNA (Best Alternative to a Negotiated Agreement) and ZOPA (Zone of Possible Agreement) to strengthen their position while maintaining long-term partnerships; and how preparation and knowledge sharing can enhance performance in complex multi-entity negotiations. The research assumes that successful negotiation in banking requires balancing three dimensions, value creation, institutional learning, and client trust, under competitive and regulatory constraints. A qualitative exploratory method was adopted. Data were collected through semi-structured interviews with four Relationship Managers and three Product Partners representing Cash Management, Treasury, and Trade functions within Bank of Tiongkok Corporation Indonesia (BTCI). Thematic analysis and coding matrices were used to identify converging and diverging negotiation patterns across roles.